1992
DOI: 10.1136/gut.33.5.687
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of ulcerative proctocolitis in Indian migrants and the indigenous population of Leicestershire.

Abstract: A retrospective epidemiological study of ulcerative colitis (UC) and proctitis was performed in Leicestershire from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
151
2
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(173 citation statements)
references
References 19 publications
13
151
2
2
Order By: Relevance
“…This observation of the increasing incidence of inflammatory bowel disease in developing countries has been made in the study by Goenka et al, 19 and in another study of Indian immigrants to the United Kingdom. 20 Other studies from the Middle East have reported similar findings. Various speculations have been made for this increase, among which are the Western lifestyle, variations in dietary intake, including refined sugar and chocolate, as well as environmental factors.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This observation of the increasing incidence of inflammatory bowel disease in developing countries has been made in the study by Goenka et al, 19 and in another study of Indian immigrants to the United Kingdom. 20 Other studies from the Middle East have reported similar findings. Various speculations have been made for this increase, among which are the Western lifestyle, variations in dietary intake, including refined sugar and chocolate, as well as environmental factors.…”
Section: Discussionsupporting
confidence: 57%
“…Inflammatory bowel disease patients are of mild-tomoderate severity. 4,5,20 Only a few patients had severe disease from the beginning, requiring occasional surgical intervention. Recurrence of colonic carcinoma was seen in 13 patients sent for surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on epidemiology of IBD done on the Indian diaspora in Britain have clearly shown that Sikhs have a higher incidence (16.5/100,000 person-years) vis a vis other ethnic/religious groups such as Hindu (10.8/100,000 person-years) or Muslim (1.8/100,000 person-years). 11,12 Hence the prevalence figures obtained in these studies may not be a true reflection of the disease burden of the whole country. Niriella et al 10 determined the incidence of UC in Sri Lanka to be 0.69/100,000 person-years.…”
Section: Prevalence and Incidence Of Ulcerative Colitis In South Asiamentioning
confidence: 87%
“…The time trends suggest that the incidence of UC has been steadily rising among Asian migrants from 1981-1994. Probert et al 11 documented the incidence and prevalence of UC in South Asians to be 13.9/100,000 person-years and 172.5 respectively in the period between 1981-1989. In the period between 1991-1994 the incidence increased from 13.9 to 17.2 in the same geographical region.…”
mentioning
confidence: 99%
“…The marked increase of IBD incidence in many countries in recent decades is incompatible with a purely genetic disease [1][2][3]. Also, data from migration studies indicate that second-generation immigrants manifest the risks of their new environment [4]. Established IBD risk factors include smoking, appendicitis, and antibiotics.…”
mentioning
confidence: 99%